2015
DOI: 10.1371/journal.pone.0124260
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Adult Pulmonary Tuberculosis in a Metropolitan City of South India

Abstract: BackgroundThe present study measured the community prevalence and risk factors of adult pulmonary tuberculosis (PTB) in Chennai city, and also studied geographical distribution and the presence of different M. tuberculosis strains in the survey area.MethodsA community-based cross sectional survey was carried out from July 2010 to October 2012 in Chennai city. Prevalence of bacteriologically positive PTB was estimated by direct standardization method. Univariate and multivariate analyses were carried out to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 18 publications
(16 reference statements)
9
87
1
1
Order By: Relevance
“…Forty surveys with 1.7 million participants in 22 countries reported the prevalence of smear-positive TB by sex [35,40,43,44,48–51,53,55,56,5860,65–67,69–71,73,74,85,87,89,90,92,94,97,101,102,105,107,110,111]. The overall random-effects weighted prevalence per 100,000 individuals was 488 (95% CI 382–623) among men and 231 (95% CI 166–321) among women for bacteriologically positive TB and 314 (95% CI 245–403) among men and 129 (95% CI 89–189) among women for smear-positive TB (S3 Table).…”
Section: Resultsmentioning
confidence: 99%
“…Forty surveys with 1.7 million participants in 22 countries reported the prevalence of smear-positive TB by sex [35,40,43,44,48–51,53,55,56,5860,65–67,69–71,73,74,85,87,89,90,92,94,97,101,102,105,107,110,111]. The overall random-effects weighted prevalence per 100,000 individuals was 488 (95% CI 382–623) among men and 231 (95% CI 166–321) among women for bacteriologically positive TB and 314 (95% CI 245–403) among men and 129 (95% CI 89–189) among women for smear-positive TB (S3 Table).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, studies carried out in India and Brazil on the spatial distribution of TB indicate that in addition to the clinical characteristics of the individual, TB is also associated with different socioeconomic factors, such as income, schooling and household quality which must be considered in the definition of strategies for TB surveillance and control 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Various international and Indian studies have found positive associations between overcrowding and poor ventilation with higher prevalence of TB. [8][9][10][11] In the present study, a considerable number of patients were exposed to inadequate ventilation [54 (46.1%)] while Overcrowding was not observed in the majority of the patients [6 (5.1%)].…”
Section: Resultsmentioning
confidence: 54%